2018
DOI: 10.1055/a-0581-8886
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic clip closure may reduce the risk of delayed bleeding after colorectal endoscopic submucosal dissection

Abstract: Background and study aims  Endoscopic submucosal dissection (ESD) has a high en bloc resection rate and is widely performed for large superficial colorectal tumors, but delayed bleeding remains one of the most common complications of colorectal ESD. The aim of the present study was to evaluate the clinical efficacy of prophylactic clip closure of mucosal defects for the prevention of delayed bleeding after colorectal ESD. Patients and methods  We enrolled consecutive patients with colorectal lesions between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Further larger controlled studies, however, are needed to validate these findings. with standard hemostatic clips or an over-the-scope-clip which remains challenging in large defects [3][4][5]. More advanced closure techniques include using clips to anchor an endoloop in a purse-string manner or hand-suturing through an overtube [6,7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further larger controlled studies, however, are needed to validate these findings. with standard hemostatic clips or an over-the-scope-clip which remains challenging in large defects [3][4][5]. More advanced closure techniques include using clips to anchor an endoloop in a purse-string manner or hand-suturing through an overtube [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…In patients requiring anticoagulation or antiplatelet agents, minimizing the risk of bleeding is even more critical, emphasizing the importance of prophylactic methods. Prior studies examining placement of hemostatic clips have shown rates of bleeding as low as 0 % in the colon, but are challenging to perform in larger defects due to the inability to adequately approximate the defect edges [3,5,14]. Furthermore, numerous clips may be required which can add significant time and cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study for large colorectal lesions (≥2 cm) has shown that prophylactic clipping decreased the risk of delayed post-polypectomy bleeding [19]. Recent studies have shown that prophylactic clip closure of mucosal defects reduced the risk of delayed bleeding after colorectal ESD [20,21].…”
Section: Bleedingmentioning
confidence: 99%
“…ESD for duodenal lesions have recently been shown to benefit from complete closure[143] as the risk of post ESD delayed bleeding and more importantly, delayed perforation (possibly caused by the high concentration of bile and digestive enzymes) can be catastrophic. Complete closure for colonic ESD is also being employed by expert centers who have reported accelerated mucosal healing[144], decreased delayed bleeding[145], as well as decreased need for post-ESD hospitalization[146]. For many of these larger closures, suturing is emerging as an alternative to clip closure[147].…”
Section: Early Gastric Cancer and Submucosal Tumors (Smts) Of The Stomentioning
confidence: 99%